Effect of twinning and detwinning on the spring-back and shift of neutral layer in AZ31 magnesium alloy sheets during V-bend. (5th March 2015) - Wang, Lifei; Huang, Guangsheng; Han, Tingzhuang; Mostaed, Ehsan; Pan, Fusheng; Vedani, Maurizio
Highlights: The detwinning behavior occurred on pre-compression samples during V-bend. The twinning was restrained on pre-stretched samples during bending. Springback increased after pre-stretch, pre-compression and annealing. Neutral layer of Mg alloys shift to outer tension region during V-bending. Coefficient of neutral layer decreased after both pre-compression and pre-stretch. Abstract: In order to investigate the effect of twinning and detwinning on springback and shift of neutral layer, pre-stretch (PRS) of 3% and 5%, and pre-compression (PRC) of 1%, 3% and 5% along rolling direction was conducted in an AZ31 magnesium alloy sheets at room temperature. 90° V-bending tests were performed at 423 K with various pre-strained samples. The results show that springback increases after both PRS and PRC deformation. The coefficient of neutral layer ( k-value ) decreases with the increase of the levels of PRS and PRC. After PRS, twinning in an inner compressive region during bending is restrained and tension–compression asymmetry decreased. After PRC, detwinning occurs which implying that it dominates the deformation in the outer tensile region, while in inner compressive region twinning still governs the deformation. Twinning and detwinning leads to a decrease of asymmetry mechanism between the outer and inner layers. The decrease of asymmetry mechanism after PRT and PRC results in a drop of the neutral layer offset.